A comunicação nas fanpages: o desafio da cidadania na interação entre deputados e cidadãos - Isidoro, Carolina Zafino (2017)
From the study of interaction and communication between federal representatives and citizens throughout 2015 in the fanpages of the three most voted in Goiás, we sought to understand if these Facebook pages are used as spaces of citizenship, expanding the exercise of communication between representatives and represented. To obtain answers, we investigate interaction as a mode of participation in democracy and strengthening of citizenship. In the development of the work, we review the concepts of citizenship, communication and interaction and the potential of digital media to promote virtual public spheres, focused on public interest debate. With the analysis of the publications of the parliamentarians and the comments published by the citizens and parliamentarians on the selected subjects, it was possible to verify that the communicational citizenship in spaces of interaction is an incremental process, that happens through the dialogue between the interacting ones. Representatives and representatives are responsible for exercising citizenship in fanpages and, consequently, in Brazilian democracy, which has in the federal deputy the power of representation of the people in decision-making.